The role of Artificial Neural Network (ANN) in predicting skin surface temperature, evaporative and convective heat losses from wet-skin surface of a cow / Zahid A. Khan … [et al.] - Khan, Zahid A.; Quadir, G.A.; Suhail, Arif; Seetharamu, K.N. (Faculty of Mechanical Engineering and University Publication Centre (UPENA), 2006)
A multi-layered feedforward fully-connected Artificial Neural Network (ANN) based on Levenberg-Marquardt training algorithm is used to predict skin temperature, evaporative and convective heat losses from a cow. The mathematical model available in the literature is used to generate training data to train the neural network. The predicted skin temperatures, evaporative and convective heat losses due to the change in level of wetness, air velocity, relative humidity and ambient air temperature using ANN agree very closely with those obtained from the mathematical model used in the analysis.